Urbanization and biodiversity of arbuscular mycorrhizal fungi: The case study of Delhi, India - Gupta, Manju M. (2018)
Increasing urbanisation is widely associated with decline in biodiversity of all forms. The aim of the present study was to answer two questions: (i) Does rapid urbanization in Delhi (India) affect biodiversity of arbuscular mycorrhizal (AM) fungi? (ii) If so, how? We measured the AM fungal diversity at nine sites located in Delhi forests, which had different types of urban usage in terms of heavy vehicular traffic pollution, littering, defecation and recreational activities. The study revealed a significant decrease in AM fungal diversity (alpha diversity) and abundance measured as spore density, biovolume, mean infection percentage (MIP) in roots, soil hyphal length and easily extractable glomalin related soluble proteins (EE-GRSP) at polluted sites. Non-metric multidimensional scaling (NMDS) and nested PERMANOVA, revealed significant differences in AM fungal community structure which could be correlated with variations in soil moisture, temperature, pH, carbon, and nitrogen and phosphorus levels. BEST (biota and environmental matching) analysis of biological and environmental samples revealed that soil temperature and moisture accounted for 47.6 % of the total variations in the samples. The study demonstrated how different forms of human activities in urban ecosystems of Delhi are detrimental to the diversity and abundance of AM fungi.